Living Economy: Relevansi Fatwa DSN-MUI tentang Online Shop dalam Etika Bisnis Seller E-commerce pada Aplikasi TikTok - Alfarisi, Muhammad Adib; Suhedi, Suhedi (TAWAZUN: Journal of Sharia Economic Law, 2023)
This study discusses e-commerce business ethics that realize business continuity, but there are problems between buyers and sellers not meeting face to face which can harm consumers. Therefore, the importance of the trust of both parties is an absolute requirement in buying and selling online. This is implementing business ethics based on the provisions of Islamic law and the presence of maqashid sharia and the DSN-MUI Fatwa regarding online shops. This study aims to analyze the application of the DSN-MUI Fatwa regarding online shops that pay attention to TikTok e-commerce business ethics. This research method is a normative research using maqashid sharia theory by Wahbah Zuhaili. The results of the study, that the authors argue find the relevance of e-commerce that is aligned with the DSN-MUI Fatwa regarding online shops as Islamic legal rules that maintain trust in sellers and buyers in the continuity of business ethics, such as the findings of fathanah ethics (professional), amanah (trusted), shiddiq (honest), and tabligh (transparent). Thus, the implications of TikTok e-commerce contribute to maintaining the stability of the continuity of seller's business ethics for the people's economy.